Staying connected on the home front: communication and well-being of civilian spouses during deployment. Issue 3 (3rd July 2019) - Meek, Nicole A.; Totenhagen, Casey J.; Hawkins, Stacy Ann; Borden, Lynne M.
ABSTRACT: In this study, we examined communication frequency via asynchronous (i.e. email/internet, postal mail) and synchronous (i.e. commercial telephone, DSN telephone, military exchange provided phone, military video phone, and video teleconference) communication methods as associated with well-being (i.e. marital quality and psychological well-being) in civilian wives during their Service member husbands' deployment in the US military ( N  = 2230). We expected a curvilinear effect, such that increased communication frequency is beneficial up to a point where it then becomes detrimental for well-being. For asynchronous communication, we did not find this curvilinear relationship and instead identified a positive linear relationship for both marital quality and psychological well-being. For synchronous communication, we found this curvilinear relationship between communication and marital quality, but no significant association with psychological well-being. Overall, this study suggests military spouses might be encouraged to utilize asynchronous communication methods such as email and postal mail very frequently and moderate "real-time" communication.